Influence of tax mentality and tax morals on condition of system of tax control in the state - R. R. Arabov (Путеводитель предпринимателя, 2020)
Tax control is important for economy. Nevertheless, need of studying ofthe reasons of this phenomenon and measurement of its consequences for the state scale taking into account influence of tax mentality and tax morals is the cornerstone of any kind of control.